(untitled) (Journal of Maternal and Child Health, 2024)
Background: Depression is a mental symptom that arises with symptoms of loss of spirit, mood swings, and disruption of daily activities. Symptoms of depression are commonly experienced by pregnant women, but symptoms of depression can be treated and prevented. Recognizing the causes or determinants of depression in pregnant women is important to prevent the onset of depressive symptoms. This study aimed to estimate the effect of planning, complications, and social support on depression in pregnant women. Subjects and Method: A systematic review and meta-analysis was conducted using PRISMA guidelines and the PICO model. The articles used are between 2017 and 2023. Population = pregnant women. Intervention = Poor planning, complications, low social support. Comparison= Good planning, no complications, high social support. Outcome = Depression. Articles are compiled from databases such as Google Scholar, PubMed, and Science Direct. Literature search using the keywords "Planned" OR "Unplanned" AND "Complication" AND "Social Support" AND "Depression" AND "Cross Sectional". A total of 19 articles met the inclusion criteria for the meta-analysis, and were further assessed using RevMan 5.3. Results: Meta-analysis using a cross-sectional study design of 16 primary study articles from Ethiopia, Greece, Portugal, Germany, Iceland, Sri Lanka, China, Nigeria, Tanzania, and Kenya with a total sample of 7234 subjects showed that poor planning (aOR= 1.89; CI 95%= 1.56 to 2.30; p< 0.001); pregnancy complications (aOR=2.00; CI 95%= 1.72 to 2.32; p< 0.001); Symptoms of depression improved in pregnant women and these results were statistically significant. Low social support (aOR= 1.24; CI 95%= 0.75 to 2.05; p< 0.400) increased depressive symptoms in pregnant women but was not statistically significant. Conclusion: Poor planning, pregnancy complications, and low social support increase depressive symptoms in pregnant women.